2010 IEEE International Conference on Industrial Technology 2010
DOI: 10.1109/icit.2010.5472583
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Active Safety Light using Virtual Test Drive within Vehicle in the Loop

Abstract: Driving at night time increases the risk of accidents because the driver's perception is reduced to the limited area of the environment which is illuminated by the car's head lights. In the study presented in this paper, the tool Vehicle in the Loop (VIL) is used the first time to research the potential of a new light function. VIL is a Virtual Reality application and simulation setup which allows for testing driver assistance systems in critical driving situations while driving a real car, but without the ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 1 publication
0
9
0
1
Order By: Relevance
“…virtual traffic participants, in order to safely test driver assistance systems [3]. Their technique was successfully used for evaluating a system, which supports drivers in evasion maneuvers [5]. Using a HMD as a HUD replacement has also been considered in the field of aerospace cockpits [9].…”
Section: Related Workmentioning
confidence: 99%
“…virtual traffic participants, in order to safely test driver assistance systems [3]. Their technique was successfully used for evaluating a system, which supports drivers in evasion maneuvers [5]. Using a HMD as a HUD replacement has also been considered in the field of aerospace cockpits [9].…”
Section: Related Workmentioning
confidence: 99%
“…Consequently, optical see-through HMDs have been used in the automotive domain to augment virtual traffic participants onto a real test setup [3]. The same system has been successfully implemented to evaluate evasion maneuver visualizations [17]. Lauber and Butz compared HMD and HUD visualizations in the car [14], revealing first insights on the particularities of using optical see through HMDs while driving.…”
Section: Huds and Hmds In The Carmentioning
confidence: 99%
“…However, the working algorithm of VIL for ADAS simulation was not published and only showed the environment in which the study was conducted. The studies in [17][18][19][20][21]31] use VIRES's Virtual Test Drive (VTD) without revealing the algorithm. [22,23] and [28] also constructed their VIL system with commercial simulation tools, CarMaker and CarSim.…”
Section: Vehicle In the Loopmentioning
confidence: 99%
“…Thomas Bock proposed a hardware configuration that links augmented reality to existing vehicle simulators [15,16]. Laschinsky has shown that it can be applied in the development of active safety lights to conduct tests in the daytime [17]. VIL is used for driver reaction of critical situations [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation